Secondary Foreign Policy: The Cooperation Role of Local and Regional Actors in Border Issues in Riau Islands - Herry Wahyudi; Azhari Setiawan; Ardi Putra (Indonesian Perspective, 2024)
The Riau Islands Province is a province that directly faces the borders of the Republic of Indonesia. The existence of the Riau Islands as a province on the border and northern gateway to Indonesia makes the Riau Islands face the dynamics of border issues. The dynamics of border issues which are in direct contact with the development of the discipline of International Relations with the presence of new actors in International Relations make border issues worthy of study. This research tries to examine the existence of new actors in international relations that have direct contact with border issues in the Riau Islands province. One of the development dynamics raised by researchers is the presence of new actors in the regions who have an important role in carrying out foreign sub-policies related to border issues, especially in the Riau Islands province. This research will discuss this phenomenon by examining the concept of secondary foreign policy used by local and regional actors in the Riau Islands province in building and designing border cooperation. This research use a descriptive qualitative approach with a literature study that focuses on a thematic approach by organizing data through bibliometric analysis. This technique is expected to be able to discover and measure secondary foreign policy concepts used by local and regional actors in the Riau Islands province in building border cooperation.